Strategi Pemasaran Digital Untuk Pengembangan Usaha Kecil - M. Rivaldi; Nabila Anastasya; Ifdah Aulia; Na’imahtul Zakiyah Dwi Wardhani; Muhammad Sofwan; Muhammad Sholeh (Journal on Education, 2024)
Now, people can connect with each other and with others around the world through the virtual world, in addition to using devices. Despite the current economic downturn, SMEs (Small and Medium Enterprises) are predicted to boost the economy. The implementation of digital technology-based marketing strategies, or digital marketing, offers potential for SMEs to grow into a significant economic force. To maximize profits, SME actors work with distribution and promotion channels based on digital platforms. Currently, almost all SMEs—including fast food companies and restaurants—use digital marketing-based promotional and distribution channels. Through the idea of empowering the people's economy, this research focuses on exploring the function of digital marketing as a marketing strategy for Small and Medium Enterprises (SMEs). This approach is a necessary adaptation for SMEs to thrive in the era of Industry 4.0 and ultimately become superior SMEs